Authentic Interpretation of The Hadith 'You Know Better About Your Worldly Affairs' - Arfan Arfan; Muhammadiyah Amin; La Ode Ismail Ahmad; Nur Afni A. (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to generate an authentic interpretation of the hadith